2004
DOI: 10.1186/1471-2105-5-186
|View full text |Cite
|
Sign up to set email alerts
|

Constraint Logic Programming approach to protein structure prediction

Abstract: Background: The protein structure prediction problem is one of the most challenging problems in biological sciences. Many approaches have been proposed using database information and/or simplified protein models. The protein structure prediction problem can be cast in the form of an optimization problem. Notwithstanding its importance, the problem has very seldom been tackled by Constraint Logic Programming, a declarative programming paradigm suitable for solving combinatorial optimization problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Since we completely omit the secondary structure information of the protein when solving the problem, these results are not comparable to those using secondary structure information (eg. [ 16 - 18 ]). All of the experiments have been performed on an Intel(R) Xeon(R) CPU E5440 at 2.83 GHz with 32 GB memory.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since we completely omit the secondary structure information of the protein when solving the problem, these results are not comparable to those using secondary structure information (eg. [ 16 - 18 ]). All of the experiments have been performed on an Intel(R) Xeon(R) CPU E5440 at 2.83 GHz with 32 GB memory.…”
Section: Resultsmentioning
confidence: 99%
“…Authors in [16,18] added some extra constraints to disallow angles of 60° and 180° for three consecutive amino acids. Also their definition of contact distance is somewhat different from us.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jafari et al [16] demonstrated that logic-based methods are useful for improving PLOS ONE static conceptual models in molecular biology. Palù et al [17] demonstrated that logic-based models can be used effectively for predicting protein structures and functions.…”
Section: Description Of Current Approachesmentioning
confidence: 99%
“…Logic-based approaches have been successfully applied to solve complex problems in bioinformatics by viewing these problems as binary classification tasks. For example, [3] achieved acceptable results for predicting protein structures using constraint logic programming techniques. [4] presented a methodology that successfully predicted the tertiary structure of a protein using constraint logic programming.…”
Section: Introductionmentioning
confidence: 99%